1994
DOI: 10.1002/pro.5560030419
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for the interaction of urea with lysozyme

Abstract: Abstract:The effect of urea on the crystal structure of hen eggwhite lysozyme has been investigated using X-ray crystallography. High resolution structures have been determined from crystals grown in the presence of 0, 0.7, 2, 3, 4, and 5 M urea and from crystals soaked in 9 M urea. All the forms are essentially isomorphous with the native type I1 crystals, and the derived structures exhibit excellent geometry and RMS differences from ideality in bond distances and angles. Comparison of the urea complex struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 20 publications
6
59
0
Order By: Relevance
“…Unlike earlier studies, no electron density corresponding to denaturant molecules were visible in any of the urea soaked structures. Also the decrease in B-factors observed earlier, for RNase A, 22 DHFR, 22 and lysozyme 21 was not observed in the present work with the exception of some regions in the 1.5 M** structure. This is probably because the present studies use denaturant concentrations close to the corresponding Cm in solution while the earlier studies were all carried out at denaturant concentrations well below the Cm.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Unlike earlier studies, no electron density corresponding to denaturant molecules were visible in any of the urea soaked structures. Also the decrease in B-factors observed earlier, for RNase A, 22 DHFR, 22 and lysozyme 21 was not observed in the present work with the exception of some regions in the 1.5 M** structure. This is probably because the present studies use denaturant concentrations close to the corresponding Cm in solution while the earlier studies were all carried out at denaturant concentrations well below the Cm.…”
Section: Discussionmentioning
confidence: 39%
“…Several lysozyme structures were solved at high resolution (1.4-1.6 Å ) and in the presence of high concentrations (up to 9 M) of urea. 21 However the crystal structures do not give any structural insight into lysozyme unfolding as the addition of urea actually increases the order in the crystal structure by stabilizing loop regions and decreasing the overall B-factors. The protein structure remains unchanged in the presence of urea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inset the k diss -GdnHCl gradient is shown to connect the slope of the stoppedflow unfolding rate of the protein, k u , as a function of GdnHCl measured at 10°C. k u values were measured by changes in tryptophan fluorescence (]) and 430 nm Soret heme absorbance(3). The arrow points to the C m of equilibrium unfolding of ferrocytochrome c at 10°C, 0.1 M phosphate, pH 7.…”
mentioning
confidence: 99%
“…Early crystallographic work suggested that urea stabilizes the flexible parts of folded proteins, and relaxes the crystal packing contacts. 10 Bhuyan 11 has also shown, using different methods, that low (mM) concentrations of urea may stabilize proteins. The thermal dissociation of CO from ferrocytochrome c was slowed at low 'salting-in' concentrations of urea or guanidine hydrochloride.…”
mentioning
confidence: 97%